The Effect of Promotion Mix on Consumer Loyalty at PT. Hadji Kalla Sidrap Branch - Ulyana Muslimin; Mulyana Machmud; Hasanuddin Hasanuddin (Institute for Research and Community Service, 2021)
This study selects the products marketed by PT. Hadji Kalla Sidrap Branch, because it uses a promotional mix which includes advertising, sales promotion, personal selling, and publicity. The purpose of this study was to determine the effect of the promotion mix on consumer loyalty at PT. Hadji Kalla Sidrap Branch. The population in this study are customers who purchase Yamaha cars at PT. Hadji Kalla, Sidrap branch. The number of samples taken in this study were 30 respondents. The results of this study indicate that from the results of the regression analysis on testing simultaneously (Test F), it turns out that the research results prove that together the promotion mix variable has a significant effect on the purchasing decision variable. This can be proven from the Fcount value of 2.883 with a significance value (sig) of 0.035 which is smaller than the significance value (sig) of 0.05.